Doping understood as a trap to get sports wins - Goicochea Elías, José Julio (2020)
The mass media are increasingly presenting cases of athletes who resort to doping as a way to gain an advantage in sports competitions. This occurs in the vast majority of times due to the increasingly high salaries and the sums that companies invest in advertising for image concept. Nobody wants to be second. Only worth first. The glory is only written by the victors. As a counterpart we did not stop being alarmed, when we appreciated how those whom we had as impeccable champions were later seen as cheating mud idols who, by an unexpected discovery, deservedly ceased to pay homage.